KOMUNIKASI DALANG DALAM KONSEP MANDALA WIWAHA ASEP SUNANDAR SUNARYA - Arthur Supardan Nalan (LP2M ISBI Bandung, 2012)
AbstractThis study suggests the findings of field research on communication made by a puppeteer of Wayang Golek Purwa, Asep Sunandar Sunarya. This study is categorized into qualitative research with a phenomenological approach. The result of the study shows that Asep Sunandar Sunarya has performed his communication competencies as a communicative puppeteer. Communication competencies owned by Asep Sunandar Sunarya to the audience is based on his experience which is called the concept of Mandala Wiwaha. The concept of Mandala Wiwaha is a concept of technique, insight, message and audience mastery. The concept of Mandala Wiwaha has made Asep Sunandar Sunarya a famous puppeteer who posses his own “popularity